AUTOFLUORESCENT TIMELINE OF SPOTS AND DOTS IN MULTIPLE EVANESCENT WHITE DOT SYNDROME. Issue Volume 16:Issues 3(2022) (5th February 2020) - Scharf, Jackson M.; Hilely, Assaf; Freund, K. Bailey; Sarraf, David
Abstract : A case of multiple evanescent white dot syndrome is presented, which uses sequential multimodal retinal imaging to illustrate the different recovery timelines of spots and dots in multiple evanescent white dot syndrome. Although both lesion types are hyperautofluorescent, the mechanism of autofluorescence is distinctive and may be explained by their contrasting pathoanatomy. Abstract : Purpose: To describe the recovery timeline of spots and dots in multiple evanescent white dot syndrome. Methods: Sequential multimodal retinal imaging including fundus autofluorescence and cross-sectional and en face optical coherence tomography was performed to track the development and resolution of spots and dots in a case of multiple evanescent white dot syndrome. Results: En face optical coherence tomography showed that the spots are the result of ellipsoid zone loss and are hyperautofluorescent due to unmasking of the underlying retinal pigment epithelium autofluorescence. Conversely, the dots are hyperreflective with cross-sectional and en face optical coherence tomography and hyperautofluorescent, which we propose may be due to accumulation of degenerated photoreceptor material including fluorophores with autofluorescent capability such as precursors of A2E. The earlier resolution of the hyperautofluorescent spots allowed for later detection of the hyperautofluorescent dots. Conclusion: This case report illustrates the different recovery timelines of spots and dots in multiple evanescent white dot syndrome. Although both lesion types are hyperautofluorescent, the mechanism of autofluorescence is distinctive and may be explained by their contrasting pathoanatomy.